O3 Is point of care testing 'unsafe in the city'?. (18th May 2015) - Currie, Susanna; Thomas, Debbie; Hatley, Alma; Rezvani, Sean; McQuillan, Orla
Abstract : Background: Point of care testing (POCT) for HIV is acknowledged in UK Guidelines as useful outside clinic settings, but is it safe? Our 10 year POCT programme has experienced false positives and negatives which resulted in our use of back up serology samples as standard; this differs from practice within POCT elsewhere. We had a televised false positive POCT result on "Unsafe Sex in the City" and 4 false positives in a year which caused a temporary shutdown of our POCT programme and an MRHA investigation. Aim: To review the need for back-up serology with POCT. Method: A retrospective review of all Alere Determine™ HIV-1/2 Ag/Ab Combo tests at a City Centre outreach service in 2013. Results were compared with concomitant serology. Results: POCT was provided for 382 patients. Three patients declined POCT; 2 POCT results were not documented; 10 did not have serology in parallel. Of the remaining 367 patients: 3 true positives (0.8%); 2 false positives (0.6%); and 3 false negatives (0.8%). Negative predictive value 99.2%; Positive predictive value 60%; Sensitivity 50%; Specificity 99.4%. Discussion: This is data providing statistics for POCT in real time. Compared to advertised values Alere is underperforming. The negative predictive value is reassuring; however, the sensitivity of the test is unacceptable. Had 3 of our patients not had back up serology, they would have been unaware of their diagnosis, receiving false reassurance and potentially causing unintentional HIV transmission. Do we take this risk on board and perform POCT without back up serology?